2015
DOI: 10.1111/den.12542
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic versus surgical treatment for pancreatic pseudocyst

Abstract: Endoscopic treatment may be the first-line treatment approach for patients with pancreatic pseudocyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 26 publications
0
31
0
1
Order By: Relevance
“…Evidence-based multidisciplinary guidelines issued by the European Society of Gastrointestinal Endoscopy (ESGE) currently stipulate that in the absence of clinical improvement, endoscopic drainage is now the first-line procedure for symptomatic WON, with endoscopic necrosectomy or minimally invasive methods (rather than open surgery) constituting the next therapeutic step[ 2 ]. Although previous studies have shown that endoscopic and surgical remedies are comparable in instances of pancreatic pseudocyst[ 3 - 7 ], endoscopic treatment of symptomatic WON (especially infected lesions) is more of a challenge. The ESGE recommends either plastic or lumen-apposing metal stent (LAMS) placement for initial endoscopic transmural drainage[ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence-based multidisciplinary guidelines issued by the European Society of Gastrointestinal Endoscopy (ESGE) currently stipulate that in the absence of clinical improvement, endoscopic drainage is now the first-line procedure for symptomatic WON, with endoscopic necrosectomy or minimally invasive methods (rather than open surgery) constituting the next therapeutic step[ 2 ]. Although previous studies have shown that endoscopic and surgical remedies are comparable in instances of pancreatic pseudocyst[ 3 - 7 ], endoscopic treatment of symptomatic WON (especially infected lesions) is more of a challenge. The ESGE recommends either plastic or lumen-apposing metal stent (LAMS) placement for initial endoscopic transmural drainage[ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore a Cochrane review comparing surgical and endoscopic treatment modalities concluded that further studies are required on this topic [ 27 ]. A recent analysis concluded that the optimal treatment for pancreatic pseudocyst is still controversial, in the absence of meta-analysis comparing the two approaches [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the laparoscopic approach should be preferred where relevant expertise is available [16]. A meta-analysis of 5 comparative studies, including 255 patients, published in 2015 and comparing endoscopic with surgical treatment for pancreatic pseudocysts concluded that the endoscopic approach may be the first line treatment [17]. The surgical group had a higher success rate than the endoscopic group (OR=0.43, 95%CI 0.2 to 0.95, p=0.04), with no statistical significant differences between the two groups regarding the adverse events (OR=0.67, 95% CI 0.33 to 1.36, p=0.27) and recurrence rate (OR=1.53, 95% CI 0.37 to 6.39, p=0.56) [ [19].…”
Section: Discussionmentioning
confidence: 99%